2023
DOI: 10.21037/tcr-22-2484
|View full text |Cite
|
Sign up to set email alerts
|

High expression of miR-107 and miR-17 predicts poor prognosis and guides treatment selection in acute myeloid leukemia

Abstract: Background:The prognostic significance of miR-107 and miR-17 in patients with acute myeloid leukemia (AML) remains unclear.Methods: A total of 173 patients with de novo AML from the Cancer Genome Atlas database were enrolled in this study and further divided into a chemotherapy group (98 cases) and an allogeneic hematopoietic stem cell transplantation (allo-HSCT) group (75 cases) according to their therapy regimen.Results: In the chemotherapy cohort, high miR-107 or miR-17 expression was associated with poorer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 54 publications
(54 reference statements)
0
4
0
Order By: Relevance
“…In the present issue, Liu et al ( 6 ) reported that high expression of miR-107 and miR-17 is associated with worse clinical outcomes in patients with AML who received chemotherapy, which was not observed in the group of patients who received allo-HSCT. When analyzed together, patients with high expression of both miR-107 and miR-17 had the worst clinical outcomes (entire cohort and chemotherapy group).…”
mentioning
confidence: 61%
See 2 more Smart Citations
“…In the present issue, Liu et al ( 6 ) reported that high expression of miR-107 and miR-17 is associated with worse clinical outcomes in patients with AML who received chemotherapy, which was not observed in the group of patients who received allo-HSCT. When analyzed together, patients with high expression of both miR-107 and miR-17 had the worst clinical outcomes (entire cohort and chemotherapy group).…”
mentioning
confidence: 61%
“…When analyzed together, patients with high expression of both miR-107 and miR-17 had the worst clinical outcomes (entire cohort and chemotherapy group). From the biological point of view, analysis of differentially expressed genes revealed a potential association of these miRNAs with the dysregulation of multiple metabolic processes ( 6 ).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…For example, in the study of Xu et al, tight associations between the high expression of TSC22D3 domain family genes playing an essential role in tumor progression with poor overall and event-free survival and drug resistance to BCL2 inhibitors in adult AML patients, especially in the chemotherapy group, have been reported [ 47 ]. The study of Liu et al demonstrated that high miR-107 or miR-17 expression levels were associated with poorer overall survival and event-free survival in the chemotherapy cohort of patients with de novo AML [ 48 ]. A special place is occupied by immunity-associated biomarkers, such as immune-related long noncoding RNAs [ 49 ] and immune microenvironment genes [ 50 ], which are closely related to resistance to immunotherapy and poor prognosis for AML patients.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, in MLL, where the abovementioned miRNAs are overexpressed, targeting both miR-17-5p and miR-19a-3p by antagomiRs reduces the ability of MLL cells to form colonies compared to non-MLL AML controls [58]. Several other studies suggested that the miR-17 cluster is associated with a poor prognosis [33,59] through several mechanisms, including the promotion of leukemic blast proliferation [60]. With regard to macrophage polarization, miR-17 and miR-20a promote an M1 phenotype by inhibiting signal-regulatory protein a (SIRPa) [60].…”
Section: Micrornas Associated With a Bad Prognosis Of Aml And M1 Pola...mentioning
confidence: 99%